(untitled) (Fiep Bulletin - online, 2014)
This study is to examine how teachers of early childhood education on the importance of play as a tool to enhance the biopsychosocial development of children. Them aim of this study is to report by observing the importance of play in the development of children 4-6 years, belonging to the CEI BEM-ME-QUER, Joinville-SC. The sample of 26children and two teachers, 18 children actively participated effectively in the 2nd period class. Activities were observed both in class room, as in physical education classes in the spaces andother venues in the educational center. The experiences lived by the children reflectthe importance of play for the construction and the formation of a more confident and participatory.